Teachers' attitudes in addressing learning difficulties in junior high school - Permatasari, Faudina; Azizah, Siti Nur (At- Ta'lim : Jurnal Pendidikan, 2025)
The professional attitude of the teacher can be seen mastery of the material, structure, concepts, and scientific mindset that supports the subject being taught, mastery of the competency standards subjects taught, mastery of competency standards and basic competencies of the subjects taught, development of subject matter competency standards and basic competencies of the subjects taught, creative development of the subject matter covered creative, continuous professional development, and utilisation of information and communication technology for self-development. information and communication technology for self-development. This research uses with descriptive qualitative approach that is a literature study that uses journals and other literature as the main object of research. as the main object of research. The results and discussion in this study are professional attitude of teachers in dealing with student difficulties can be overcome in various ways, namely Teachers as managers of instruction, meaning as managers of teaching, using media and methods in learning, providing spirit and motivation to learn students provide remedial and enrichment programmes.